Pembatasan Penerapan Local Content Requirements oleh Negara Berkembang Sebagai Konsekuensi Ketentuan Trims dalam Kerangka Perdagangan Internasional - Rahmadani, Novia (Media Hukum Indonesia (MHI), 2026)
The restriction of Local Content Requirements (LCR) within the international trade regime presents a significant challenge for developing countries that rely on such policy instruments to strengthen their domestic industries. Under the WTO’s Trade-Related Investment Measures (TRIMs) Agreement, LCR is deemed inconsistent with the principles of National Treatment and the prohibition of quantitative restrictions, thereby limiting the ability of developing countries to pursue industrialization. This study aims to examine how TRIMs restrict the implementation of LCR and to analyze the legal and economic implications of these restrictions on industrial policy. Using a normative juridical method with a conceptual approach through literature and development theory analysis, the study finds that LCR restrictions reduce policy space, slow technology transfer, weaken domestic supply chains, and increase import dependence. It concludes that these restrictions are not merely legalistic but structurally impactful, necessitating alternative policies that remain compliant with WTO rules.